Study of Air Humidity and Air Temperature Tutorial Room at the Faculty of Technical and Vocational Education - Zol Arini, Hafizul Hakim; Abdullah, Nurul Hidayah Liew (Research and Innovation in Technical and Vocational Education and Training, 2025)
High humidity and hot temperatures can cause discomfort to residents, especially when the weather becomes excessively hot, while frequent rain also affects air humidity. Uncontrolled temperatures not only impact physical comfort but can also affect students learning. Hot temperatures can disrupt students thoughts and emotions, decreasing productivity. Therefore, this study measured air humidity and room temperature using air conditioning in the FPTV tutorial rooms. The design of this study is experimental. Data were collected using the Testo 605 i and Testo 405 i measurement tools. This study was conducted in the Faculty of Technical and Vocational Education (FPTV) building in Block B, which includes tutorial room 1, tutorial room 2, tutorial room 3 and tutorial room 4. The method of data analysis will be presented in the form of tables or graphs and categorized according to their respective classes. The findings indicate that the air humidity and temperature are within acceptable ranges according to ICOP IAQ 2010. However, some readings did not comply with the ICOP IAQ 2010 standards, particularly in the afternoon when readings ranged from 20.0°C to 22.8°C due to changes in rainfall and the number of students present in the tutorial rooms. In conclusion, this study found that the air humidity in the FPTV tutorial rooms is at an optimal level and complies with ICOP IAQ 2010, while the air temperature showed some readings outside the specified range. The impact of this study can serve as a guide for students to adapt to the humidity and temperature in a room. The faculty management should also play an important role in ensuring a conducive environment throughout the teaching and learning process.